Agrarian Law in Land Dispute Resolution in Indonesia - Ismail Halomoan Harahap; Khotibul Umam (AT-TAFAHUM: Journal of Law, 2020)
Land disputes remain one of the most significant legal issues in Indonesia due to increasing land demand, limited land availability, weak law enforcement, and deficiencies in the land administration system. These disputes create legal uncertainty, hinder social welfare, and negatively affect sustainable development. This study aims to examine the causes of land disputes in Indonesia and analyze appropriate dispute resolution mechanisms from the perspective of Indonesian agrarian law. The research employs a normative juridical (library research) method using statutory and conceptual approaches. Primary legal materials include Law Number 5 of 1960 concerning Basic Agrarian Principles and other relevant regulations, while secondary materials consist of books, scientific journals, and previous studies related to agrarian law and land dispute resolution. The collected legal materials were analyzed qualitatively using a descriptive-analytical method. The findings reveal that land disputes are primarily caused by overlapping land ownership, weak land registration and administration systems, inconsistent implementation of agrarian regulations, limited public legal awareness, and increasing competition over land resources. In addition, disputes frequently arise between individuals, corporations, and government institutions due to conflicting ownership claims and development projects. The study also finds that litigation often requires considerable time and expense and may not provide satisfactory outcomes for all parties. Conversely, mediation and other non-litigation mechanisms offer more effective, efficient, and mutually beneficial solutions by encouraging dialogue, consensus, and the preservation of social relationships. Therefore, strengthening law enforcement, improving land administration through digitalization, enhancing legal awareness, and prioritizing mediation are essential to achieving legal certainty, justice, and sustainable land governance in Indonesia.